Epidemiological Studies of Subclinical Mastitis in Dairy Goats in Lumajang Regency, East Java, Indonesia - Fatmawati, Mira Fatmawati; Lucia Tri Suwanti; Mufasirin; Mirni Lamid; Nunuk Dyah Retno Lastuti; Endang Suprihati; Mustofa Helmi Effendi; Anam Al Arif; Widi Nugroho; Masdiana C Padaga (Faculty of Animal Science, Universitas Brawijaya, 2023)
Subclinical mastitis is an economically important disease in dairy goat farming. Lumajang is a center for dairy goats in East Java. However, routine examination of subclinical mastitis for screening tests has no data. This study aimed to provide prevalence data and identification factors that influenced subclinical mastitis. Therefore, this study was carried out as part of the national surveillance program. The research design is a cross-sectional study with simple random sampling. Samples came from 19 farms with a total individual sample of 224 dairy goats. Detection of subclinical mastitis using an undirect test with the California Mastitis Test (CMT). Identification of management factors and characteristics that can influence subclinical mastitis in dairy goat farms using a structured questionnaire. The results showed that the prevalence of subclinical mastitis in Lumajang District was 36.2%. There was a significant difference in subclinical mastitis in each village (p<0.05). The highest prevalence of subclinical mastitis was in Kandangtepus village. A farmer's characteristic factor that significantly influences subclinical mastitis is the farmer's experience. The aspect of livestock management that significantly affects subclinical mastitis is structured work management. Subclinical mastitis was prevalent in dairy goats in Lumajang District and requires prevention efforts. Prevention approach through education for farmers to increase knowledge, attitude, and socialization to improve livestock management.